Metabolomics and transcriptomics to decipher molecular mechanisms underlying ectomycorrhizal root colonization of an oak tree - Sebastiana, M. (2021)
Supplementary Information The online version contains supplementary material available at https:// doi. org/ 10. 1038/ s41598- 021- 87886-5